Infants and Children who Experience From Rectal Prolapse - Muhammad Younas Khan, Syed Asad Maroof, Fayaz Iqbal, Wardah Saleem, Muhmmand Shoaib, Kifayat, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim and Objective: to understand the outcomes of treating pediatric rectal prolapse with injection sclerotherapy using 5% phenol in almond oil. Setting & Design: Department of Pediatric Surgery MTI / LRH, Peshawar, Pakistan. A- Descriptive Study the duration of study from June 2021 to June 2022 Material & Method: In Pediatric Surgery, rectal prolapse is a prevalent issue with various potential solutions. Injection sclerotherapy was one of the techniques studied in this analysis of treatments for children with rectal prolapse. Patients who have had complete prolapse for more than three months were considered. Patients were checked in 24 hours before surgery. Before the procedure began, a Kleen Enema was administered. This operation was done while the patient was under general anesthesia. Sclerotherapy was performed by injecting a solution of 5% phenol in almond oil. While the patient was unconscious, an injection was placed in the rectum's submucosa. 8-10mL of a 5% phenol in almond oil solution was injected at 3-4 linear locations. Every patient was monitored for a whole month to look for signs of recurrence. Results: A total of 42 individuals were seen. There were 32 men and ten women among the total number of patients. Children as young as two years old and as elderly as eight years old were involved. A prolapse might endure between three months to four years. For 26 people, chronic diarrhea was a recognized problem. Sclerotherapy injections were administered to a total of 26 patients. There were no issues from the anesthesia or the procedure itself. There was no evidence of a recurrence during the one-month follow-up. Practical implication: This study will review our experience with the treatment of rectal prolapse in children and to formulate a management strategy based on outcome. Conclusions: Rectal prolapse may be successfully treated securely, affordably, and efficiently with injectable therapy using 5% phenol and almond oil. Keywords: Recto Prolapse, Sclerotherapy, children, injectable therapy, Sclerotherapy